ModeLab - Web Tool for the Modeling of Bus Rapid Transit Systems (2021)
Bus rapid transit (BRT) systems have in recent years become a viable and effective option for solving the mobility problems in different cities around the world. For these systems to fulfill their mission effectively and efficiently, they need to respond adequately to the different situations that appear periodically or arbitrarily in the users’ routines, modification of system resources (e.g., buses, drivers, lanes, or roads), among others. Modeling and simulation in these and many other complex systems are key tools to support decision-making since, in general, they are an inexpensive option that allows to quickly evaluate the effect of different changes on the system and to define the best solution in the shortest time for a specific problem or situation. This paper introduces ModeLab, a web-based tool for modeling BRT systems that facilitates the design of models by using an iconic language closer to the modeler, a language based on the real-world objects found in this type of system and that allows us to define simpler and more compact models, which are easier to visualize, understand, and configure. To evaluate the models that ModeLab can define, a model of medium complexity was developed and compared with the model obtained by ARENA®; the results show a significant reduction in the complexity of the models, while, at the same time, there are identical results when simulating the models with SIMAN (a common simulation software for both tools).